THE INFLUENCE OF WORK COMPETENCE, WORK DISCIPLINE AND WORK SATISFACTION ON EMPLOYEE PERFORMANCE IN PT SARI KREASI INDONESIA - Laidy, Yenny; Anita; Kelvin; Ghoward, Dhevin; Steven; Khairani, Rafida (STIE Kusuma Negara, 2019)
PT. Sari Kreasi Indonesia is a company engaged in the sale of food and beverages (Food and Beverages). The purpose of this study was to examine and analyze the effect of supervision, communication, work stress and employee performance at PT. Sari Kreasi Indonesia. Declining employee performance due to lack of supervision, communication is not good and employees are experiencing stress at work. The population and sample in this study amounted to 62 employees. The research method uses multiple linear regression analysis techniques. The results showed that the value of supervision was obtained tcount > ttable or 2.130 > 2.002 and significant obtained 0.037 < 0.05. The communication value has tcount > t table or 3.694 > 2.002 and the significance obtained is 0.000 < 0.05. The value of work stress tcount > ttable or 2.681 > 2.002 and the significance obtained 0.010 < 0.05. The test results obtained calculated F value (14.711) > F table (2.76) and a significance probability of 0.000 < 0.05. The results of the determination coefficient test of 0.403 this means that 40.3% of the variation in employee performance can be explained by variations in supervision, communication and work stress while the remaining 59.7% is explained by other variables not examined in this study, such as career development, job analysis, training and so on. The conclusion in this study shows that supervision, communication and work stress partially have a positive and significant effect on employee performance at PT. Sari Kreasi Indonesia (Food and Beverages). Simultaneously supervision, communication and work stress have a positive and significant effect on employee performance at PT. Sari Kreasi Indonesia (Food and Beverages).